Patent Remedies - Shapiro, Carl (American Economic Review, 2016)
Since the Supreme Court's eBay decision in 2006, the U.S. has employed a hybrid patent remedy system that mixes property and liability rules. When the patent owner and the infringer are competitors, the courts typically issue a permanent injunction requiring the infringer to cease its infringing activities. In contrast, when the patent owner and the infringer are not competitors, the courts often allow the infringer to continue its infringing activities so long as it pays specified ongoing royalties to the patent holder. This article studies the incentives for invention and for new product development in such a hybrid system.